1996
DOI: 10.1159/000244366
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Parameters in Cord Blood Indicating Early-Onset Sepsis

Abstract: Different immunologic parameters were measured in cord blood to test their usefulness in the early diagnosis of early-onset sepsis. Cord blood levels of circulating intercellular adhesion molecule-1 (cICAM-1), interleukin-6 (IL-6) and interleukin-8 (IL-8) were significantly elevated in septic compared to nonseptic neonates. No significant difference between either population was seen for cord blood C3a and elastase-α1-proteinase inhibitor complex (Eα1PI). Measured concentrations of cICAM-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
27
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 20 publications
3
27
0
1
Order By: Relevance
“…Several recent studies have explored the utility of measurement of two or more analytes for diagnosis of neonatal infection (11)(12)(13)17). For example, we have shown that CRP Ͼ 6 mg/liter and soluble ICAM-1 Ͼ 300 ng/ml in combination in plasma samples collected under endotoxin-free conditions (12,13) were independent predictors of infection and gave both a high sensitivity for clinical infection (95%) and an NPV of 97% (12).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Several recent studies have explored the utility of measurement of two or more analytes for diagnosis of neonatal infection (11)(12)(13)17). For example, we have shown that CRP Ͼ 6 mg/liter and soluble ICAM-1 Ͼ 300 ng/ml in combination in plasma samples collected under endotoxin-free conditions (12,13) were independent predictors of infection and gave both a high sensitivity for clinical infection (95%) and an NPV of 97% (12).…”
mentioning
confidence: 94%
“…Biomarkers are identified through a four-step process of discovery by appropriate multiplex biochemical analysis followed by replication ideally in independent cohorts, validation of diagnostic sensitivity and specificity, and translation into a clinical diagnostic test (9). Numerous candidate biomarkers have been identified in neonatal sepsis: elevated plasma or serum levels of inter-leukin 6 (IL-6) 1 (11,13), tumor necrosis factor ␣ (TNF␣) (11,13), neutrophil elastase (NE) (14), C-reactive protein (CRP) (12,15), soluble CD14 (16,17), granulocyte colony-stimulating factor (G-CSF) (18), soluble intercellular adhesion molecule-1 (ICAM-1) (12), and soluble L-selectin (19) have shown association with infection in neonates. The value of physiological measurements in this context has also been examined recently (20).…”
mentioning
confidence: 99%
“…EOBI is usually defined as occurring up to 72 h after birth (2) and is associated with a high morbidity and mortality risk (1). The nonspecific clinical signs as well as the currently established biochemical and hematologic parameters have their diagnostic limitations (3,4) [reviewed in (5,6)]. …”
mentioning
confidence: 99%
“…Most recent attention has focused on the measurement of cytokines including interleukin-6 (IL-6) [5][6][7], tumour necrosis factor (TNF) [5][6][7] and granulocyte colony-stimulating factor (G-CSF) [9]. However, studies have also evaluated neutrophil elastase [4], C-reactive protein (CRP) [3,5], soluble CD14 [8] and soluble intercellular adhesion molecule-1 (sICAM-1) [5].…”
Section: Introductionmentioning
confidence: 99%